Role of ICTs in knowledge management for development - Denning, Stephen (2002)
Opines that while the market is now generating a variety of out-of-the-box knowledge management tools which facilitate the sharing of knowledge, care should be taken before investing in them to ensure the relevant organisation has the capacity to take advantage of them.